Pequenas centrais hidrelétricas no rio Sapucaí-mirim (sp): diversidade e estrutura genética de Astyanax lacustris - Silva, Caio Felipe da [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
O rio Sapucaí-mirim está localizado na bacia do alto rio Paraná e apresenta uma grande diversidade de peixes neotropicais. Dentre eles, encontra-se a espécie Astyanax lacustris, popularmente conhecida como “lambari-do-rabo-amarelo”, abundante na região. A bacia do alto rio Paraná vêm enfrentando construções de inúmeras Pequenas Centrais Hidrelétricas (PCHs) e pouco se sabe a respeito do seu impacto nas populações naturais. Marcadores moleculares microssatélites são amplamente utilizados em estudos de diversidade e estruturação genética, principalmente devido a sua codomiância, abundância no genoma dos eucariotos e polimorfismo. Dado o exposto, o presente estudo analisou a diversidade e estrutura genética de populações naturais de A. lacustris coletadas a montante (reservatório da PCH de Palmeiras) e a jusante (escada da PCH de Retiro) nos anos de 2018 e 2019 utilizando marcadores microssatélites, afim de se ter mais dados a respeito do impacto dos barramentos nessas populações naturais de peixes. Sete loci microssatélites foram aplicados e programas computacionais foram utilizados para as análises. Os resultados mostraram, que de maneira geral, os quatro estoques amostrados apresentaram uma alta diversidade genética e afirmou-se a eficiência desses marcadores. No que se diz respeito a estruturação genética, foram detectados três grupos diferenciados entre si: um grupo à montante (reservatório da PCH de Palmeiras) e dois grupos amostrados a jusante, nos anos de 2018 e 2019, respectivamente. A alta diversidade genética pode ser explicada, além da capacidade dessa espécie de se adaptar a condições ambientais hostis, a práticas de repovoamento por técnicas de supportive breeding. Um outro fator que pode ter levado a esse resultado é que ambas PCHs foram contruídas recentemente. O fato das escadas das PCHs brasileiras apenas permitiram a passagem no sentido jusante-montante, pode explicar o fato da diferença populacional encontrada entre os estoques das escada da PCH de Retiro (jusante) entre os anos e a diferença da mesma com o grupo identificado a montante. Por fim, este trabalho ressalta a importância da implamentação de medidas mitigadoras, além de servir como base para futuros trabalhos, uma vez que os estudos de monitoramento inicial e contínuo de diversidade e estrutura de peixes são escassos no Brasil.

Introduction: Sepsis is among the most common reasons for hospitalization in intensive care units (ICUs) around the world, with Sepsis-induced acute kidney injury (SAKI) being considered one of the most serious and frequent complications of this condition. The assessment of nutritional needs, including resting energy expenditure (REE), as well as the monitoring of nutritional therapy in relation to the adequacy of protein caloric intake is a crucial point in critical patient care and is related to better outcomes. Objectives: To describe and compare REE estimated by the Harris Benedict formula and measured by indirect calorimetry of septic patients without associated AKI, with AKI without the need of dialysis and with dialytic AKI, and to evaluate the adequacy of the caloric intake and its association with the outcome of death. Methods: Prospective observational cross-sectional study evaluating patients with a diagnosis of sepsis admitted to an ICU of HCFMB-UNESP, aged> 18 years old, use of mechanical ventilation, with FiO2 <0.6, and with prescription of enteral or parenteral nutrition therapy, during 24 consecutive months. Patients were divided into three groups (group 1: sepsis without associated AKI; group 2: sepsis and AKI; group 3: sepsis and dialytic AKI) and had the EG estimated by the HB equation and determined by the IC. In the evaluation of caloric adequacy, energy adequacy values between 70 and 100% of the caloric needs were considered as goal and the adequacy of the protein intake was> 80% of the needs. Results: A total of 125 patients with a diagnosis of sepsis were evaluated. Of these, 67.2% (n = 84) were of the male gender, with age of 62.53 ± 16.55 years old, presence of septic shock in 58.4%, pulmonary focus as the main infection site (67.2%) and AKI present in 80% of the septic population, with 49.6% with dialytic need. No statistically significant difference was observed between the groups without and with AKI, on dialysis or not, in relation to the REE measured (p = 0.33) and estimated (p = 0.88). Sepsis without AKI (n = 25), sepsis with AKI (n = 43), and sepsis with dialytic AKI (n = 57) presented medium REE statistically higher than estimated (1855.0 (1636.75 - 2052.75) vs. 1551.0 (1349.0-1719.25), p = 0.007, 1868.0 (1219.5- 2344.75) vs.1388.0 (1254.0-1665.5), p = 0, 02 and 1986 (1477-2419) vs. 1426 (1270-1715), p <0.001 respectively). In the three groups studied there was a predominance of caloric intake inadequacy, represented by 72% (n = 18) of septic patients without AKI, 79% (n = 34) of septic patients with AKI and 74% (n = 42) of septic patients with dialytic AKI, with no significant difference between groups (p = 0.75). As for protein, there were predominance of individuals with inadequate protein intake in both sepsis group without AKI (60%, n = 15), and the sepsis groups with AKI (67%, n = 29) and sepsis with dialytic AKI (65%, n = 37), with no significant difference between groups (p = 0.82). Caloric (p <0.001) and protein (p <0.001) intake and caloric adequacy (p <0.001) were statistically higher in the group that evolved to hospital discharge, and the caloric adequacy was considered a protective factor of mortality (OR: 0.96; 95% CI: 0.94-0.97). Conclusion: There was no statistically significant difference between the groups related to GER measured by CI and estimated by HB, suggesting that the sepsis presence exerts a greater influence on REE increase than the presence of AKI and dialysis. The groups presented REE measured statistically higher than estimated. None of the groups presented caloric and protein adequacy according to needs. Caloric inadequacy was identified as an independent risk factor for death of septic patients with or without AKI in the ICU.
Small hydroelectric power plants on the Sapucaí-Mirim River (SP): diversity and genetic structure of Astyanax lacustris
Keywords: Barramentos; Microssatélites; Diversidade genética